Pengaruh Kemudahan Penggunaan, Harga Dan Promosi Terhadap Loyalitas Pelanggan Pada Pengguna Shopee - Arjuna Putra; Muhammad Nur Fietroh (Advantage: Journal of Management and Business, 2023)
This study aims to examine the Effect of Ease of Use, Price and Promotion on Customer Loyalty for Shopee users. The population in this study is the people of Sumbawa City. The sample of this research is 100 respondents who have several criteria. The sampling technique used is Non Probability Sampling. The data analysis used was the classical assumption test, multiple linear regression test, hypothesis test (t/effect test) and the coefficient of determination test and processed using the SPSS 25 program. The results of this study indicate that there is a positive and significant influence on Ease of Use, Price and Promotion of Customer Loyalty